Housing price variation analysis in Malaysian scenario / Suhaily Maizan Abdul Manaf ... [et al.] - Abdul Manaf, Suhaily Maizan; Mohd Said, Nur Shafini; Omar Ali, Siti Rapidah; Adenan, Nur Dalila (2018)
Housing price variation has been in top of macroeconomic problems. Factors like unstable and unreasonable pricing, and homeless phenomenon are increasing from year to year. This study will examine the determinants of housing price volatility in Malaysia by taking into consideration of the yearly data of 34 years from 1982 to 2016 by employing descriptive statistics, regression model and correlation method analysis. Housing price acts as a dependent variable, and the findings show that gross domestic product (GDP) has significant relationship and interest rate gives positive correlation with housing price. Contradicting with the result, the inflation rate (INF) and unemployment rate (UNEMPL) are found insignificant in influencing the volatility of housing in Malaysia while, the result for net income per capita (NI) is found as the most significant. The outcome of the study is useful in providing the future research direction towards the variation of housing price in Malaysia.